Implementasi nilai tasawuf dalam pembinaan sikap santri di Pesantren Luhur Malang - Nabilah, Reza Lailatul (Maliki Interdisciplinary Journal, 2024)
There are many problems that occur in teenagers, such as the erosion of moral and ethical values can be seen from the much impulsive behaviour of teenagers in facing problems. This can make teenagers lose healthy thought patterns and behaviour in living life. The implementation of Sufism values ​​in adolescent behaviour needs to be improved to form moral and ethical individuals. The focus of the research in this article is: (1) what model of Sufism is taught at Islamic Boarding School Luhur Malang? (2) How are the values ​​of Sufism implemented at Islamic Boarding School Luhur Malang? (3) What are the results of the application of Sufism values ​​at the Luhur Malang Islamic Boarding School? The purpose of writing this article is to find out the implementation of Sufism values ​​in developing the attitudes of students who are also students at the Luhur Islamic Boarding School, Malang. The results of the research that has been carried out are information that the values ​​of Sufism taught at Islamic Boarding School Luhur Malang are the values ​​of repentance, the concept of asceticism, and patience. Implementing Sufism values ​​at the Luhur Malang Islamic Boarding School is through istighosah and educational media with the implementation model of takhalli, tahalli, and tajalli.